Pemberdayaan Kewirausahaan Kelompok Wanita Tani (KWT) dalam Pengembangan Inovasi Produk Makanan (Desa Cipedes, Kecamatan Ciniru, Kabupaten Kuningan) - Setiawan, Iyan; Luviantika, Irsa; Dandi; H, Siska Aulia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to implement a women farmer empowerment program in Cipedes Village through the innovation of traditional sagon food processing to enhance entrepreneurial skills. The methods used in this study include training, mentoring, and evaluation of women's farmer groups (KWT) in producing and marketing sagon more innovatively. The results show that innovations in sagon processing, including taste, shape, and packaging, have successfully increased market interest in this product. Furthermore, providing training and guidance on using digital technology for marketing has improved the entrepreneurial knowledge and skills of KWT members. This program has not only contributed to increasing household income but also strengthened the role of women farmers in local economic development. Therefore, empowering women farmers through the innovation of traditional food processing like sagon has great potential to be further developed as a model for economic empowerment in rural areas.